(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2024)
Warri-Effurun is one of the oil regions in the Niger Delta and has experienced industrial expansion with upsurge in population growth in the last five decades. The attendant effect of such growth is synonymous with more groundwater pumping needed to satisfy domestic, industrial and other purposes. The consequence is the subjection of aquifers to intensive abstraction of groundwater to meet the water needs of the inhabitants. The high demand for groundwater may be worsened by the climate change. The impact of climate change on groundwater is complex but can better be understood by modeling. The study used groundwater modeling software to understand groundwater flow pattern under high groundwater over-abstraction under climate change conditions. Model scenarios output revealed that pumping is sustainable when the aquifer was recharged with 2*10-4mm/year of precipitation and pumping rate of 6.1776m3/day, groundwater flow is towards the Warri River. However, flow direction was reversed when pumping rate was increased geometrically to 13,590.72m3/day with zero net recharge (drought conditions precipitated by climate change). The reversal in the flow direction is indicative of interaction between groundwater and river water. The implication is that contaminants may be transported from the river into the aquifer, consequently compromising groundwater quality and thus making it unsuitable for drinking. The study concludes that groundwater modeling is a better tool in understanding how stressed aquifer under the influence of climate change may respond to heavy groundwater over-pumping.